2019
DOI: 10.1161/circulationaha.118.034624
|View full text |Cite
|
Sign up to set email alerts
|

A Premature Termination Codon Mutation in MYBPC3 Causes Hypertrophic Cardiomyopathy via Chronic Activation of Nonsense-Mediated Decay

Abstract: Background: Hypertrophic cardiomyopathy (HCM) is frequently caused by mutations in myosin binding protein C3 (MYBPC3) resulting in a premature termination codon (PTC). The underlying mechanisms of how PTC mutations in MYBPC3 lead to the onset and progression of HCM are poorly understood. This study's aim was to investigate the molecular mechanisms underlying the pathogenesis of HCM associated with MYBPC3 PTC mutations by utilizing human isogenic induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 34 publications
(49 reference statements)
6
87
0
Order By: Relevance
“…We used a single-cell traction force microscopy approach with additional controls for geometric shape (7:1 rectangular micropatterns as opposed to row micropatterns) and myofibrillar density (using concurrent live-cell actin imaging) that might also account for differences. Our finding of restoration of MyBP-C protein-level stoichiometry is similar to the recently reported findings by Seeger et al (11), who also reported no difference in maximal contractile force in engineered cardiac tissues derived from a heterozygous MYBPC3-mutant iPSCM line containing a nonsense mutation, consistent with our results. However, in contrast to that work, we did not find evidence of dysregulation of calcium handling or NMD in the several MYBPC3-mutant iPSC lines that we generated, and we found a constant rate of NMD between heterozygous and homozygous C-terminal mutation lines.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We used a single-cell traction force microscopy approach with additional controls for geometric shape (7:1 rectangular micropatterns as opposed to row micropatterns) and myofibrillar density (using concurrent live-cell actin imaging) that might also account for differences. Our finding of restoration of MyBP-C protein-level stoichiometry is similar to the recently reported findings by Seeger et al (11), who also reported no difference in maximal contractile force in engineered cardiac tissues derived from a heterozygous MYBPC3-mutant iPSCM line containing a nonsense mutation, consistent with our results. However, in contrast to that work, we did not find evidence of dysregulation of calcium handling or NMD in the several MYBPC3-mutant iPSC lines that we generated, and we found a constant rate of NMD between heterozygous and homozygous C-terminal mutation lines.…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported that heart tissue from patients with tissue-level myocardial hypertrophy and MYBPC3 frameshift or splice mutations exhibit an approximately 40% reduction in MyBP-C protein. However, we also previously demonstrated no reduction of MyBP-C in an embryonic stem cell model with a frameshift mutation, similar to a recent report from an iPSC model (10,11). Therefore, we first quantified MyBP-C levels in patient and genome-engineered iPSCMs at 25 days after differentiation using mass spectroscopy to establish whether protein-level compensation is attained in the present models.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Activation of mitogen-activated protein kinase kinase 1/2 (also known as MEK1/2), but not extracellular-signal-regulated kinase 1/2 (ERK1/2), induced the formation of abnormal cardiomyocyte structure whereas extracellular-signal-regulated kinase 5 (ERK5) caused an enlarged cardiomyocyte phenotype. In another study, CRISPR/Cas9 and TALENs were used by Seeger et al (2019) to investigate the molecular mechanisms underlying HCM associated with mutations in the MYBPC3 gene that introduce premature stop codons [78]. iCMs containing these mutations exhibited aberrant Ca 2+ handling and other molecular dysregulations not due to haploinsufficiency of MYBPC3 protein.…”
Section: Studying Disease Pathophysiologymentioning
confidence: 99%